3 2x 1 )-( x 4 )= 3x 5
![3 2x 1 )-( x 4 )= 3x 5](https://media.cheggcdn.com/study/bcd/bcdc024f-f7a7-4c14-9210-3b6aae72ea3e/image.jpg)
- 2 x 4 )- 3 2x 1 )=- 3x 5
- 3 2x 1 )- 5 x 3 )+ 6 3x 4 )= 26
- 3 2x 1 )- 5 x 3 )+ 6 3x 4 )= 83
- 2 2x 1 )- 3 3x 5 )= 4 x 5 )- 8
- 3x 1 4 2x 3 5 1 x 10
- 5x 4x 3x 2x x =- 1 2 3 4 5
- 5x 4 3x 3 2x 2 1 x 2 4
- 3 2x 1 )- 5 x 3 )+ 6 3x 4 )= 24
- 3 2x 1 2 6 3x 5 4 x
- 3 x 2 )- 5 2x 1 )- 2 3x 4 )- 4 0
- 3 2x 1 )- 5 x 3 )+ 6 3x 4 )- 19x
- X 3 2x 1 4 5x 6 3x
- 3 x 2 )- 5 2x 1 )- 2 3x 4 )+ 10 0
- X 3 2x 4 4x 5 3x 1
- 6 x 2 1 )-( 2x 4 )( 3x 2 3 5x 21